Nutritional vulnerability in zoeal stages of the yellowline arrow crab Stenorhynchus seticornis (Brachyura: Majoidea) - Barros-Alves, Samara P. [UNESP]; Alves, Douglas F. R. [UNESP]; Antunes, Mariana [UNESP]; López Greco, Laura S.; Negreiros-Fransozo, Maria Lucia [UNESP] (CSIRO Publishing, 2018)
Knowledge of the critical points in larval stages is essential to evaluate the physiological state of the larvae in their natural environment. This study investigated the nutritional vulnerability index (NVI) of the first (ZI) and second (ZII) zoeal stages of Stenorhynchus seticornis. Zoeae were assigned to two experiments: (1) point of no return (PNR), consisting of treatments with increasing days of starvation and subsequent days of feeding; and (2) point of reserve saturation (PRS), consisting of treatments with increasing days of feeding and subsequent days of starvation. There were two control groups: continuous starvation (CS) and continuous feeding (CF). Mortality was used to estimate the time when 50% of initially starved larvae (PNR 50) lost the ability to moult to the next stage and when 50% of initially fed larvae (PRS 50) were capable of moulting to the next stage. The mean (±s.d.) development time of ZI and ZII under CF was 4.4 ± 1.2 and 5.1 ± 1.8 days respectively. Mortality in the CF groups was 30 and 52% for ZI and ZII respectively. For ZI, PNR 50 and PRS 50 were 1.0 ± 0.0 and 2.1 ± 1.0 days respectively. The estimated NVI for ZI was 2.2, which indicates that S. seticornis depends on exogenous food and is considered planktotrophic during the first larval stage.
Keywords: Decapoda; experimental zoology; Inachidae; nutrition; plankton